How old is too old to work for physicians? - Kimak, Agnieszka; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
The healthcare systems throughout the world are facing numerous problems, including aging and shortages of medical staff. Although senior medical practitioners are important to the healthcare, their competency may decline with age. A major problem experienced nowadays by some elderly practitioners is digital exclusion caused by difficulties with adopting new technologies. Some attempts are being made to determine the optimum moment to retire, considering its possible impact on the safety and wellbeing of patients, as well as on the health system and human resource allocation. Until legal regulations are adopted, the age-related screening programs can be used to determine the optimal retirement age.